2022
DOI: 10.1021/jacs.2c03138
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Sugar Nucleotides from Common Sugars by the Cascade Conversion Strategy

Abstract: Sugar nucleotides are essential glycosylation donors in the carbohydrate metabolism. Naturally, most sugar nucleotides are derived from a limited number of common sugar nucleotides by de novo biosynthetic pathways, undergoing single or multiple reactions such as dehydration, epimerization, isomerization, oxidation, reduction, amination, and acetylation reactions. However, it is widely believed that such complex bioconversions are not practical for synthetic use due to the high preparation cost and great diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 94 publications
(126 reference statements)
1
36
0
Order By: Relevance
“…Recently, it was reported that such cost-effectiveness (and hence viability for multienzyme cascades) had been further improved through regeneration of the required cofactors (NADH, NADPH, NAD + , PMP, and acetyl-CoA, Figure ). , This has recently been exemplified through the synthesis of 25 challenging to access NDP-sugars starting from mannose, sucrose, and N -acetylglucosamine, in high yield, on a multigram scale, and without the need for purifications. , Additionally, the use of polyphosphate kinase (PPK3) or pyruvate kinase (PK) allows for the regeneration of the nucleotide triphosphates using phosphate glass or phosphoenolpyruvic acid (PEP) as sources of phosphate (Figure ). Both methods were effective at regenerating ATP used by sugar kinases and UTP/GTP utilized by NDP-sugar pyrophosphorylases.…”
Section: Using Biocatalysis To Provide the Building Blocks For Bioche...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that such cost-effectiveness (and hence viability for multienzyme cascades) had been further improved through regeneration of the required cofactors (NADH, NADPH, NAD + , PMP, and acetyl-CoA, Figure ). , This has recently been exemplified through the synthesis of 25 challenging to access NDP-sugars starting from mannose, sucrose, and N -acetylglucosamine, in high yield, on a multigram scale, and without the need for purifications. , Additionally, the use of polyphosphate kinase (PPK3) or pyruvate kinase (PK) allows for the regeneration of the nucleotide triphosphates using phosphate glass or phosphoenolpyruvic acid (PEP) as sources of phosphate (Figure ). Both methods were effective at regenerating ATP used by sugar kinases and UTP/GTP utilized by NDP-sugar pyrophosphorylases.…”
Section: Using Biocatalysis To Provide the Building Blocks For Bioche...mentioning
confidence: 99%
“…Recently, it was reported that such cost-effectiveness (and hence viability for multienzyme cascades) had been further improved through regeneration of the required cofactors (NADH, NADPH, NAD + , PMP, and acetyl-CoA, Figure 2 ). 81 , 82 This has recently been exemplified through the synthesis of 25 challenging to access NDP-sugars starting from mannose, sucrose, and N -acetylglucosamine, in high yield, on a multigram scale, and without the need for purifications. 81 , 82 Additionally, the use of polyphosphate kinase (PPK3) or pyruvate kinase (PK) allows for the regeneration of the nucleotide triphosphates using phosphate glass or phosphoenolpyruvic acid (PEP) as sources of phosphate ( Figure 2 ).…”
Section: Using Biocatalysis To Provide the Building Blocks For Bioche...mentioning
confidence: 99%
“…A lot of marine bacterial pigments were investigated for antimicrobial, anti-inflammatory, antioxidant, anti-HSV-1, anticancer, antidiabetic, and wound healing activities, indicating their potential biomedical applications as well as food, feed, cosmetic, and pharmaceutical formulations [ 8 , 9 , 12 ]. In addition, the natural marine pigments and other secondary metabolites could be used as “green chemistry” to replace synthetic compounds [ 11 , 12 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wild-type SALTY RmlA accepts diverse α- d -hexose-1-phosphates, including all monodeoxy α- d -Glc-1-phosphates, to produce various dTDP-sugars . Elegant work by Thorson and co-workers demonstrated that rational and evolved mutations in SALTY RmlA could provide access to an even broader pool of NDP-sugars, including ADP- and GDP-sugars and dTDP-unnatural sugars. Others have expanded this nucleotide sugar pool through the use of RmlA homologues that also demonstrate a lack of substrate specificity. , While diverse nucleotide sugars have been produced through chemoenzymatic routes, there have been limitations in the efficiency of a single enzyme to produce different NDP-sugars, especially with noncanonical substrates. , …”
mentioning
confidence: 99%
“…32−36 Others have expanded this nucleotide sugar pool through the use of RmlA homologues that also demonstrate a lack of substrate specificity. 2,37−39 While diverse nucleotide sugars have been produced through chemoenzymatic routes, 40 there have been limitations in the efficiency of a single enzyme to produce different NDP-sugars, especially with noncanonical substrates. 25,26 One key limitation to the catalytic efficiency of RmlA is product inhibition by dTDP-α-Glc or negative feedback regulation by dTDP-β-L-Rha via allosteric site binding (Figure 1B).…”
mentioning
confidence: 99%